Android-Based Control System of Lawn Mower Using Bluetooth Connection - Asmara Yanto; Anrinal Anrinal; Prasetyo Subekti (LP2M - Institut Teknologi Padang, 2020)
The purpose of this research is to build and test the android-based control system of lawn mower using Bluetooth connection. The lawn mower has 4 DC motor actuators, where a DC motor for moving the rear wheels that serves to move the lawn mower back and forth, a DC motor to drive the front wheels that serves to turn the lawn mower, a DC motor to adjust the cutting blade elevation and a DC motor for turning the cutter blade. The four DC motors are controlled by a Arduino. The command or input to control the motion of the mower is sent via Android with a bluetooth connection to Arduino. The lawn mower control system testing is carried out to cut the grass. From the tests was conducted, it can be concluded that the lawn mower control system works well.